Exploration of lentiviral vectors and TAT-fusion proteins for the delivery of XIAP protein to neonatal retinal progenitor cells - Szymanska, Irena (University of Ottawa (Canada), 2008)
Post-transplant apoptosis is a major obstacle to successful cell replacement therapy for retinitis pigmentosa. Over-expression of the X-linked inhibitor of apoptosis (XIAP) protein could increase transplant survival leaving a greater numbers of cells available to replenish photoreceptors lost during retinal degeneration. Sonic Hedge hog expanded C57BL/6 mouse neonatal retinal progenitor cells (Hh-RPCs) were infected with two lentiviral constructs, encoding XIAP/GFP or GFP only, as well as with the TAT-fusion protein, TAT-eGFP. The optimal delivery conditions and expression patterns were assessed. It was found that lentiviral infection, in conjunction with fluorescence activated cell sorting (FACS) allowed for the creation of a nearly pure line of Hh-RPCs which over-expressed XIAP protein for at least one month. Although the TAT-fusion protein efficiently transduced Hh-RPCs, its nuclear localization made it unsuitable for XIAP protein delivery. These results demonstrated two methods of transducing primary retinal progenitor cells and represent an important first step towards efficient cell replacement therapy in the retina.
Keywords: Biology, Cell.; Biology, Animal Physiology.; Chemistry, Biochemistry.